PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN TOTAL ASSET TURN OVER TERHADAP DEVIDEND PAYOUT RATIO DAN IMPLIKASI PADA HARGA SAHAM PERUSAHAAN LQ 45 - TITA DEITIANA (Jurnal Bisnis dan Akuntansi, 2013)
This research is aimed to know the influence of financial performance to management decision in paying devidend to the stock holder. The determinants of share prices have been investigated by scholars and practitioners by employing a variety of methods and factors. This study investigates the internal determinants of the share price movement on sector basis. The purpose of this study is to empirically study the effect of current ratio, return on equity and total asset turn over on dividend payout ratio and the implications with share price at the firm LQ 45 on Indonesia Stock Exchange. Sampling Method used in this study is the method of purposive sampling. The number of samples used in this study based on the criteria of a total from 45 firms registered on IDX in the analysis more than less 20 are used as samples for this study. The Study was conducted in the period 2008-2011. This result of the study using path analysis finds that the total asset turn over effects the dividend payout ratio. While the return on equity effects on share price. The research showed the company fundamental, its financial aspect became consideration to the payment of dividend and there is implication at share prices.